Experimental and DFT investigation on the influence of electron donour/acceptor on the hydrogen bonding interactions of 1-(1,3-Benzothiazol-2- y1)-3-(R-benzoylthiourea) - Muhd Hafizi Zainal,; Wun, Fui Mark-Lee; Syahidah Mohd Tahir,; Ishak Ahmad,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The presence of two different chromophores in benzothiazole molecule namely benzothiazole and aromatic rings lead to interesting chemical and biological properties that attract more researches on the compounds. Three new benzothiazolyl-benzoythiourea compounds namely 1-(1,3-benzothiazol-2-yl)-3-(benzoylthiourea) (BBT), 1-(1,3-benzothiazol-2-yl)-3-(4-chlorobenzoylthiourea) (BBT-4Cl) and 1-(1,3-benzothiazol-2-yl)-3-(4-methoxybenzoylthiourea) (BBT-4OCH3) with different electron withdrawing substituents (R) at the para positions on the benzene ring of benzoylthiourea ring have been synthesized from the reaction of R-benzoyl isothiocyanate (R= H, Cl, and OCH3) and 2-aminobenzothiazole. The compounds were characterized by spectroscopic techniques (infrared, 1H proton NMR and UV-Vis). The IR spectra showed the frequency signals of n (C=O), n (C=S), n (N-H) at 1664-1673, 1238-1249 and 3031-3055 cm-1, respectively. The 1H proton NMR spectra showed the presence of N-H amine and amide signals in the region of (12.14-12.35) and (14.17-14.43) ppm, respectively. The proton signals of the two benzothiazole and benzoylthiourea moieties appear at 7.08-8.16 ppm. A theoretical study based on Density Functional Theory (DFT) and Time-Dependent (TD) DFT was conducted to optimize the geometrical structure and investigate the electronic properties of title compounds. The highest occupied molecular orbital (HOMO) was found on the benzothiazole moiety; while, the lowest-unoccupied molecular orbital (LUMO) was located at the benzoylthiourea fragment. The DFT optimized structures possessed an intramolecular hydrogen bonding and the types of para substituents used influenced the properties of hydrogen bonding.